Pharmacoeconomic Evaluation of Using One-Molar Gadolinium-Based Magnetic Resonance Contrast Agent Compared to Half-Molar Agents for the Diagnosis of Multiple Sclerosis - A. A. Alikhanov; N. L. Shimanovskiy (Вестник рентгенологии и радиологии)
Objective: to conduct a comparative assessment of the pharmacoeconomic advantages of using gadobutrol in comparison with half-molar (0.5 M) gadolinium chelates for the diagnosis of multiple sclerosis (MS).Material and methods. A calculator was developed in Microsoft Excel, in which the number of exacerbations of multiple sclerosis was obtained when using one-molar (1.0 M) gadolinium-based contrast agents (GBCAs) and 0.5 M gadolinium chelates, and pharmacoeconomical results were analyzed by conducting a cost analysis and a budget impact analysis. The analysis took into account only direct medical costs (research costs (administering of GBCAs) and hospitalization costs due to exacerbations) funded under the mandatory health insurance system. The results have been calculated for a cohort of 1.000 patients.Results. The analysis of pharmacoeconomic effectiveness showed that magnetic resonance studies of the central nervous system using gadobutrol were characterized by a reduction in the number of MS exacerbations by 70 cases. In the cost analysis the use of gadobutrol in both patients less than 75 kg (7.5 ml administered volume) and more than 75 kg (15 ml administered volume) demonstrated a reduction in total costs compared to 0.5 M gadolinium chelates (gadodiamide, gadoteric acid, and gadoteridol). Budget impact analysis showed that the transfer of 1.000 patients with studies using 0.5 M GBCAs on the gadobutrol due to the reduction in the incidence of MS exacerbations leads to budgetary savings in the group of patients under 75 kg from 4.264.610 to 6.565.827 RUB, and in patients more than 75 kg from 2.267.767 to 6.870.201 RUB.Conclusion. As a result of pharmacoeconomical modeling, it was found that the use of gadobutrol for central nervous system studies for the diagnosis of MS in comparison with using 0.5 GBCAs can reduce the number of MS exacerbations and lead to money savings.